United Arab Emirates : 2009 Article IV Consultation; Staff Report; Public Information Notice; and Statement by the Executive Director for United Arab Emirates. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The United Arab Emirates (UAE) was adversely affected by a series of external and domestic shocks in 2009, including the global economic slowdown, the shutdown of international capital markets, and the impact of the bursting Dubai property bubble in mid-2008. Oil receipts plummeted, global trade and logistics contracted, as did property and construction activities. Executive Directors have welcomed the ongoing engagement with Dubai World's creditors and stressed the importance of a speedy, orderly, cooperative, and predictable approach to debt restructuring.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet